Al-Muwajahah al-Hadhariyyah wa Shurah al-Gharb fi al-Riwayah al-Arabiyyah al-Haditsah - Riwayah Ezz al-Din Shukri Fashir Anamudzajan (Dirasah Naqdiyyah Tathbiqiyyah) / The Civilizational Confrontation and The Image of The West in The Modern Arab Novel - The Novels of Ezz al-Din Shukri Fashir as A Model (An applied critical study) - Sanaa Soliman Saeed (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The research dealt with the civilizational confrontation and the image of the West in the modern Arab novel, and I took the novels of Ezz al-Din Shukri Fashir as a model to explain these civilizational gaps and the relationship of influence and influence of the different cultural patterns. The research came in two sections and a conclusion. The first section dealt with: ways of life and representations of the civilizational gap. The second section dealt with the West through fictional characters. The conclusion came it contains the most important results that I reached: Amog them: 1) Representations of the civilizational gap emerged in Ezz al-Din Fashir’s novels between the East and the West, and its manifestations varied, such as the concept of health care and citizen rights, the nature of Western thought and its view of life, and the nature of interaction between people. 2) Ezz al-Din Fishir was keen to approach Western civilization from an intellectual angle, and to rely on the principle of benefit, which justifies the means to reach the end. 3) Western society and the concept of globalization emerged in the author's novels. The Western ruling system is adopting a methodology that re-standardizes the human race. According to studied data and concepts aimed at unifying identity among the human race. 4) The author discussed the issue of fascination with Western civilization, and its locations were numerous in his novels, making clear to the reader the tendency of the Arab person, and other conquered peoples, to imitate the dominant, especially language and fashion, which reflects psychological defeat and a feeling of inferiority. 5) The author’s fictional characters expressed the image of the West, in a way that reflected his perceptions in the fields of: science, fashion, and human rights. Hence, the author’s novels surrounded multiple angles of Western civilization.المستخلص: تناول البحث المواجهة الحضارية وصورة الغرب في الرواية العربية الحديثة، وقد اتخذت من روايات عز الدين شكري فشير أنموذجًا لبيان تلك الفجوات الحضارية وعلاقة التأثير والتأثر للأنساق الثقافية المختلفة، وجاء البحث في مبحثين وخاتمة، فتناول المبحث الأوَّل: أساليب الحياة وتمثُّلات الفجوة الحضارية. وتناول المبحث الثَّاني: الغرب عبر الشخصيات الروائية. وجاءت الخاتمة: وفيها أهم النتائج التي توصلت إليها؛ منها: 1) برزت تمثُّلات الفجوة الحضارية في روايات عز الدين فشير بين الشرق والغرب وتباينت مظاهرها، كمفهوم الرعاية الصحية وحقوق المواطن، وطبيعة الفكر الغربي ونظرته للحياة، وطبيعة التعامل بين البشر. 2) حرص عز الدين فشير على تناول الحضارة الغربية من الزاوية الفكرية، واعتماده على مبدأ المنفعة الذي يبرر الوسائل للوصول للغاية. 3) برز المجتمع الغربي ومفهوم العولمة في روايات المؤلف؛ إذ تنتهج المنظومة الغربية الحاكمة منهجية تعيد تنميط الجنس البشري؛ وفقًا لمعطيات ومفاهيم مدروسة تهدف لتوحيد الهوية بين الجنس البشري. 4) ناقش المؤلف قضية الانبهار بالحضارة الغربية، وتعددت مواضعها في رواياته، فتجلى للقارئ ميل الإنسان العربي، وغيره من الشعوب المغلوبة، لتقليد الغالب، وخصوصًا اللغة والأزياء، مما يعكس هزيمة نفسية وشعورًا بالدونية. 5) عبَّرت الشخصيات الروائية لدى المؤلف عن صورة الغرب، على النحو الذي عكس تصوراته في مجال: العلم، الأزياء وحقوق الإنسان، ومن ثم، جاءت روايات المؤلف تحيط بزوايا متعددة من الحضارة الغربية.